Facile synthesis of Co3O4 nanoparticles with different morphology for efficient water oxidation in alkaline media. Issue 1 (1st April 2022) - Li, Zhengsheng; Guo, Ruitang; Lin, Zhidong; Ji, Xiangyin; Yuan, Ye; Hong, Longfei; Pan, Weiguo
Abstract: Hydrogen production from water electrolysis is an important measure to achieve clean and sustainable energy in the future. Oxygen evolution reaction is a half-reaction of water electrolysis process, and its efficiency has a great influence on the overall reaction. The morphology of the catalyst has a great influence on the catalytic performance of the catalyst for oxygen evolution, but the mechanism of the effect of the morphology on the activity is still unclear. Therefore, the influence of the catalyst morphology on the catalytic activity needs to be studied urgently. Co3 O4 is widely used in oxygen evolution reactions. Therefore, we took three Co3 O4 with different morphologies as the research objects to study the effect of morphology on the oxygen evolution activity of Co3 O4 . The results show that among the three different morphologies of cobalt tetroxide, the Co3 O4 with porous sheet morphology exhibits the best oxygen evolution activity (η10 = 1.54 V in 1 M KOH). The reason for the better activity of cobalt tetroxide with the morphology of the hollow sheet may be due to its larger specific surface area and more active sites, which reduces the reaction electron transfer barrier. Our work sheds new light on the design of novel oxygen evolution electrocatalysts.